Relationship of Symptom-Onset-to-Balloon Time and Door-to-Balloon Time With Mortality in Patients Undergoing Angioplasty for Acute Myocardial Infarction - Cannon, Christopher P; Gibson, C. Michael; Lambrew, Costas T; Shoultz, David A; Levy, Drew; French, William J; Gore, Joel M; Weaver, W. Douglas; Rogers, William J; Tiefenbrunn, Alan J (JAMA : the journal of the American Medical Association, 2000)
CONTEXT Rapid time to treatment with thrombolytic therapy is associated with lower mortality in patients with acute myocardial infarction (MI). However, data on time to primary angioplasty and its relationship to mortality are inconclusive. OBJECTIVE To test the hypothesis that more rapid time to reperfusion results in lower mortality in the strategy of primary angioplasty. DESIGN Prospective observational study of data collected from the Second National Registry of Myocardial Infarction between June 1994 and March 1998. SETTING A total of 661 community and tertiary care hospitals in the United States. SUBJECTS A cohort of 27,080 consecutive patients with acute MI associated with ST-segment elevation or left bundle-branch block who were treated with primary angioplasty. MAIN OUTCOME MEASURE In-hospital mortality, compared by time from acute MI symptom onset to first balloon inflation and by time from hospital arrival to first balloon inflation (door-to-balloon time). RESULTS Using a multivariate logistic regression model, the adjusted odds of in-hospital mortality did not increase significantly with increasing delay from MI symptom onset to first balloon inflation. However, for door-to-balloon time (median time 1 hour 56 minutes), the adjusted odds of mortality were significantly increased by 41% to 62% for patients with door-to-balloon times longer than 2 hours (for 121-150 minutes: odds ratio [OR], 1.41; 95% confidence interval [CI], 1.08-1.84; P=.01; for 151-180 minutes: OR, 1.62; 95% CI, 1.23-2.14; P<.001; and for >180 minutes: OR, 1.61; 95% CI, 1.25-2.08; P<.001). CONCLUSIONS The relationship in our study between increased mortality and delay in door-to-balloon time longer than 2 hours (present in nearly 50% of this cohort) suggests that physicians and health care systems should work to minimize door-to-balloon times and that door-to-balloon time should be considered when choosing a reperfusion strategy. Door-to-balloon time also appears to be a valid quality-of-care indicator.